The use of euphemisms in Ancient Storybook of Indonesia Korea 1 Hanguk Indonesia Yetiyagi 1 - Adhea Tsabitah Sulistiyo; Yulianeta Yulianeta; Velayeti Nurfitriana Ansas (Journal of Korean Applied Linguistics, 2023)
Korean students and beginner-level Korean learners often use harsh language because they often learn from shows that use coarse language. Therefore, this study of euphemism aimed to describe (1) variations of euphemisms in the form of words or sentences, taboos, cultural traits, social discrimination, and negative situations (2) the functions of using euphemisms in the book Ancient Korean Indonesian Stories 1. This research is a qualitative descriptive research. The data were analyzed through data reduction, data display, and pulling a conclusion or verification. Data validity was obtained from data triangulation. The data were analyzed based on the theory of the form and function of euphemism by Kim Mi Hyeong. This research shows the following results. First, the euphemisms of words 86%, and sentences 14%. Forms of euphemisms based on taboo is 71%, (2) social discrimination 10%, (3) negative situations 19%, and zero data were found in the form of cultural traits. Second, the euphemism function (1) the self-protection function is 9%, (2) the purification function is 43%, which is the most dominant function contained in the data in the object of this study. Second, the euphemism function (1) the self-protection function is 9%, (2) the purification function is 43%, which is the most dominant function found in this object of study. (3) control maintenance and social order 29%, (4) protection role 5%, (5) and function change in meaning 14%, and there was no data found on the function of the need for new terminology.